Cu- and Al-Decorated Monolayer TiSe2 for Enhanced Gas Detection Sensitivity A DFT Study - Xiao, Landong (Langmuir : the ACS journal of surfaces and colloids, 2023)
The rapid industrial development has contributed to worsening global pollution, necessitating the urgent development of highly sensitive, cost-effective, and portable gas sensors. In this work, the adsorption of CO, CO2, H2S, NH3, NO, NO2, O2, and SO2 gas molecules on pristine and Cu- and Al-decorated monolayer TiSe2 has been investigated based on first-principles calculations. First, the results of the phonon spectrum and ab initio molecular dynamics simulations demonstrated that TiSe2 is dynamically stable. In addition, compared to pristine TiSe2 (-0.029 to -0.154 eV), the adsorption energy of gas molecules (excluding CO2) significantly decreased after decorated with Cu or Al (-0.212 to -0.977 eV in Cu-decorated TiSe2, -0.438 to -2.896 eV in Al-decorated TiSe2). Among them, NH3 and NO2 have the lowest adsorption energies in Cu and Al-decorated TiSe2, respectively. Further research has shown that the decrease in adsorption energy of gas molecules is mainly due to orbital hybridization and charge transfer between decorated Cu and Al atoms and gas molecules. These findings suggest that TiSe2 decorated with Cu and Al can effectively improve its sensitivity to NH3 and NO2, respectively, making it promising in gas sensing applications